Universalism and Locality in Sally Rooney’s Digital Ireland - McAteer Michael (Open Library of Humanities, 2025)
Text messages and emails permeate the novels of contemporary Irish author Sally Rooney, shaping the ways in which characters relate to one another while also reflecting the globalization of Irish society through the medium of digitalization. In light of the socialist political positions that some of her principal characters adopt, this article examines digital communication in Conversations with Friends and Normal People with reference to certain concepts of Marx. I address online modes of communication in both novels in terms of Marx’s understanding of relations between workers and machines in the industrial era, Christian Fuchs’ re-articulation of his ideas for the age of digital capitalism, and the critique of empty universalism that Marx directs against the modern liberal-democratic political state. I examine Rooney’s narration of tensions between rural/small-town and urban life in Ireland as part of the online environment through which she addresses these issues. Observing the significance of Edna O’Brien’s The Country Girls (1960) to her first two novels, I stress how important local Irish attachments are to Rooney’s fiction, both as a means of resisting empty universalism and as testimony to human exploitation in the present age of digital capitalism.